The relation between innovation sources and ICT roles in facility management organizations. Issue 4 (26th August 2014) - Scupola, Ada
Abstract : Purpose: – The purpose of this paper is to present research findings on the relation between internal/external sources of innovation and information and communication technology (ICT) as a supporter/enabler of facilities management (FM) organizations, as well as on the strategic orientation towards open innovation of FM organizations. Design/methodology/approach: – This study uses a qualitative research approach. The data collection includes qualitative semi-structured interviews with key FM managers and directors and secondary material such as company brochures, reports and information provided on the participating companies' websites. Findings: – The results show that the FM organizations in the study sample are starting to develop and engage in open FM service innovations, even though they still mostly conduct closed innovation activities. The findings show that FM organizations mostly take an ambidextrous strategic orientation towards FM service innovations, while they also embrace an exploration approach. Concerning the role of ICT in FM service innovations, the study shows that in the explorative organizations, ICT was mostly an enabler, while in the ambidextrous organizations, ICT mostly supported and enabled the innovations in question. Only in two innovation instances was ICT identified as having a utility role. Practical implications: – The findings of this study challenge researchers and managers to rethink how and why a strategic orientation towards innovation, the sources of innovation and the role of ICT might affect service innovation in FM organizations. One important implication for FM managers and researchers is the importance that the government might have as an external source in fostering FM service innovations, especially in light of changing environmental requirements, such as energy consumption. FM managers should also consider how they could use ICT to improve and innovate FM services and service delivery and the kind of sources (external/internal) they should use to carry out this task. Originality/value: – This paper contributes to the empirical and theoretical understanding of the sources of innovation and ICT as a supporter/enabler, as well as the strategic orientation towards innovation in FM organizations.